Ukrainian Antarctic Research: Current Bibliography (January 2009–October 2010) - V. P. Rybachuk; N. G. Videnina (Ukrainian Antarctic Journal, 2010)
The bibliographic descriptions of the Ukrainian scientific works on Antarctica that were published domestically and abroad in 2009 and 20010 as well as additional materials issued in 2008 are listed herein. This bibliographic data extends and complements the 2007–2009 current bibliography of national publications, presented in the "Ukrainian Antarctic Journal" in 2009 (issue 8). The abstracts were collected from Ukrainian scientific journals, collections, and conference proceedings as well as national (“Dzherelo”, “Litopys zhurnal'nykh statej”, etc.) and international (“Antarctic Bibliography”, Scopus, Google scholar, Scirus, e-Library) bibliographic databases. In total 148 publications were compiled on the topics of Antarctic research within the last two years. The references were arranged under the subject headings based on those used by the scientific issue "Ukrainian Antarctic Research" (V.P. Rybachuk, P.F. Gozhik, N.G. Videnina, and V.A. Litvinov, Ed. P.F. Gozhik, 2008, Kiev, Varta Publishers, 286 p., ISBN 978-966-02-4803-8).